DOES INTERNATIONAL TRADE AFFECT WELFARE? ECONOMIC FIQH ANALYSIS OF UMAR BIN KHATTAB - muslikhati muslikhati; Imamul Hakim (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2019)
International trade in the era of globalization is essential. With international trade, the world economy becomes interconnected (Sharing economic) and interdependent. This study aims to find out and analyze how much influence international trade has on improving domestic welfare. The method used in this study is the PLS method, which is a type of multivariate research. International trade as an independent variable and welfare variable as the dependent variable is a construct of the overall model. Trade variables are indicated by FDI and Net export variables, while welfare variables are indicated by variables of income, consumption and wealth. From the results of this research, it was found that the construct variable namely international trade as an independent variable had a significant effect on the dependent variable, welfare. While the indicators for each variable, namely the value of FDI and Net exports, has a significant impact on international trade variables. Likewise with welfare indicators, namely the level of income, consumption and wealth also affect welfare.